Coating structure and film thickness measurement method
The coating structure with an auxiliary member allows precise film thickness measurement of heat-foamed coatings on diverse bases, ensuring uniform carbonized insulation and consistent heat resistance.
Patent Information
- Application Number
- JP2021031319
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-01
- Publication Date
- 2025-01-31
- Estimated Expiration
- 2041-03-01
AI Technical Summary
Existing methods fail to accurately measure the film thickness of heat-foamed coating layers on various bases, including non-metal materials, which affects the consistency of heat-resistant protection performance.
A coating structure is developed with a laminated heat-foamed coating layer on a base, featuring an auxiliary member with a metal material on its surface, fixed using stoppers or adhesives, allowing for precise film thickness measurement using electromagnetic or overcurrent methods.
The structure enables stable measurement of film thickness regardless of base type, ensuring consistent heat-resistant protection by forming a uniform carbonized insulation layer during high temperatures.
Smart Images

Figure 0007624846000001 
Figure 0007624846000002 
Figure 0007624846000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a novel coating structure and a method for measuring film thickness. [Background technology]
[0002] In order to protect the base of steel frame materials, steel materials, etc., which constitute buildings, from fire, various thermally foamable coating materials have been proposed that foam due to a rise in temperature during a fire or the like, and form a carbonized insulation layer. As such thermally foamable coating materials, those made by blending a foaming agent, a carbonizing agent, a flame retardant, etc. with a synthetic resin are known. The heat-resistant protective performance of a thermally foamable coating material is often determined by its coating thickness, and in order to obtain the desired heat-resistant protective performance, it is important to form a coating of a predetermined thickness uniformly on the base surface. In general, the thickness of a thermally foamable coating material layer formed on the base surface of steel frame materials, steel materials, etc. is measured using an electromagnetic or eddy-current type coating thickness meter (for example, Patent Document 1 and Patent Document 2).
[0003] Meanwhile, in recent years, in order to further improve the heat resistance and protective performance of buildings, the formation of a thermally foamable coating layer on various substrates such as concrete, mortar, wood, synthetic resins, fibrous materials, etc. in addition to steel frame materials and steel materials has been considered. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2003-088799 A [Patent Document 2] JP 2018-159065 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, depending on the type of base, there are cases where the film thickness cannot be measured or cannot be measured accurately. The present invention has been made in consideration of such problems, and has an object to provide a coated structure in which the film thickness of a thermally foamable coating material can be measured regardless of the type of base. [Means for solving the problem]
[0006] In order to solve these problems, the inventors discovered that in a structure in which a thermally foamable coating material layer is laminated on a base, by fixing a specific auxiliary member to the base surface, it is possible to measure the film thickness of the thermally foamable coating material regardless of the type of base, and thus completed the present invention.
[0007] That is, the present invention has the following features. 1. A coated structure in which a thermally foamable coating material layer is laminated on a substrate, the substrate being a nonmetallic material, The non-metallic material is a fiber-based insulation material or a foamed plastic insulation material; A support member is provided on the surface of the base. Using a stopper The auxiliary member is fixed to the support member, and the auxiliary member has a metal material on at least its upper surface. The fastener is fixed to the base by piercing the base, A covered structure, comprising a thermally foamable covering material layer laminated on the base so as to cover the auxiliary member. 2. The head has an area of 1 cm 2 2. The coated structure according to 1, characterized in that the thickness is 0.1 μm or more and 5 mm or less. 3. 2. The covering structure according to 1, wherein the fastener has a length of 5 to 100 mm and is shorter than the thickness of the base. 4.1 above. From any of the above 3. A method for measuring the thickness of a thermally foamable coating layer in the coated structure described in claim 1, characterized in that the distance from the surface of the thermally foamable coating layer to the head of the auxiliary member is measured by an electromagnetic or eddy-current type thickness meter. 5. A method for forming a coated structure in which a thermally foamable coating material layer is laminated on a substrate, comprising: Pierce the stopper The method includes a step of applying a thermal foaming coating material to the base material after fixing the auxiliary member, the base material being a non-metallic material, The non-metallic material is a fiber-based insulation material or a foamed plastic insulation material; the auxiliary member has a metal material at least on its upper surface, A method for forming a covered structure, comprising applying a thermally foamable covering material to the base so as to cover the auxiliary member. Effect of the Invention
[0008] The structure of the present invention can stably measure the thickness of the thermally foamable coating material regardless of the type of substrate. This makes it possible to stably obtain the desired heat-resistant protection performance when the temperature rises due to a fire, etc. [Brief description of the drawings]
[0009] [Figure 1] An example of the covering structure of the present invention is shown. [Diagram 2] An example of the covering structure of the present invention is shown. [Diagram 3] 1 shows an example (enlarged view) of a coated structure of the present invention. [Figure 4] An example of the covering structure of the present invention is shown. [Diagram 5] 1 shows an example (enlarged view) of a coated structure of the present invention. [Figure 6] An example of the film thickness measuring method of the present invention will be described. [Figure 7] An example of the covering structure of the present invention is shown. [Explanation of symbols]
[0010] 1. Base 2. Thermal foaming coating layer 3. Auxiliary parts 31. Glue 32. Fastener 4.Base material 41. H-shaped steel frame 5. Film Thickness Gauge DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The present invention will be described in detail below based on the embodiments.
[0012] <Covering structure> Fig. 1(I) is a cross-sectional view showing an example of the coated structure of the present invention. In Fig. 1(I), a thermally foamable coating layer 2 is laminated on a substrate 1. An auxiliary member 3 is fixed to the surface of the substrate 1, and the thermally foamable coating layer 2 is laminated so as to cover the auxiliary member 3.
[0013] Fig. 1 (II) is a cross-sectional view showing another example of the coated structure of the present invention. As shown in Fig. 1 (II), the base 1 may be a laminate of a base material 4 such as a steel frame material or a steel material constituting a building. Specifically, in Fig. 2, the base 1 is coated on an H-shaped steel frame 41, an auxiliary member 3 is fixed to the base 1, and a thermally foamable coating material layer 2 is laminated so as to cover the auxiliary member 3.
[0014] (Base) The base 1 of the present invention is characterized by being a non-metallic material. Examples of non-metallic materials include wood materials; inorganic materials such as lightweight mortar, lightweight concrete, calcium silicate board, ALC board, siding board, gypsum board, slate board, concrete, and mortar; and insulation materials such as fiber insulation materials such as glass wool, rock wool, cellulose fiber, and insulation board, and foamed plastic insulation materials such as polyethylene foam, polystyrene foam, and polyurethane foam. In particular, the present invention can stably measure the thickness of the thermal foaming coating layer 2 formed on the surface of flexible materials such as fiber insulation materials and foamed plastic insulation materials, so that the desired heat-resistant protection performance can be stably obtained.
[0015] The thickness of the above-mentioned base 1 is not particularly limited, but is preferably 5 to 500 mm (more preferably 10 to 300 mm). In the present invention, even if the base 1 has a thickness, the thickness of the thermally foamed coating material layer formed on the surface can be stably measured, so that the desired heat-resistant protective performance can be stably obtained. In the present invention, "α to β" is synonymous with "α or more and β or less".
[0016] (Thermal foaming coating layer) The thermally foamable coating layer 2 of the present invention is formed by a thermally foamable coating material that foams when the ambient temperature rises due to a fire or the like and the coating temperature reaches a predetermined foaming temperature (preferably 150°C or higher, more preferably 180°C or higher, and even more preferably 200 to 400°C) and forms a carbonized heat insulating layer in that temperature range. As such a thermally foamable coating material, one containing a resin component, a flame retardant, a foaming agent, a carbonizing agent, and a filler as constituent components is preferable.
[0017] Examples of the resin component include water-dispersed, water-soluble, NAD, solvent-soluble, and solventless types, and are not particularly limited to one-liquid and two-liquid types. Specific examples include organic synthetic resins such as vinyl acetate resin, vinyl acetate / vinyl ester versatic acid copolymer resin, vinyl acetate / ethylene copolymer resin, vinyl acetate / vinyl ester versatic acid / acrylic copolymer resin, vinyl acetate / acrylic copolymer resin, acrylic resin, acrylic / styrene resin copolymer resin, epoxy resin, urethane resin, polyester resin, polybutadiene resin, alkyd resin, and vinyl chloride resin. These may be used alone or in combination.
[0018] The flame retardant of the present invention generally exhibits at least one of the following effects in the event of a fire: dehydrating and cooling effect, non-flammable gas generation effect, carbonization promotion effect, etc., and has the effect of suppressing the combustion of the resin component. The flame retardant used in the present invention is not particularly limited as long as it has such an effect, and known flame retardants can be used. For example, organic phosphorus compounds such as tricresyl phosphate, diphenyl cresyl phosphate, diphenyl octyl phosphate, tri(β-chloroethyl) phosphate, tributyl phosphate, tri(dichloropropyl) phosphate, triphenyl phosphate, tri(dibromopropyl) phosphate, chlorophosphonate, bromophosphonate, diethyl-N,N-bis(2-hydroxyethyl)aminomethyl phosphate, and di(polyoxyethylene)hydroxymethyl phosphonate; chlorine compounds such as chlorinated polyphenyl, chlorinated polyethylene, diphenyl chloride, triphenyl chloride, pentachlorinated fatty acid ester, perchloropentacyclodecane, chlorinated naphthalene, and tetrachlorophthalic anhydride; antimony compounds such as antimony trioxide and antimony pentachloride; phosphorus compounds such as phosphorus trichloride, phosphorus pentachloride, ammonium phosphate, and ammonium polyphosphate; and boron compounds such as zinc borate and sodium borate. These can be used alone or in combination of two or more. In addition, although an uncoated product can be used, a coated product can also be used.
[0019] The mixing ratio of the flame retardant is preferably 50 to 1000 parts by weight, more preferably 100 to 800 parts by weight, and more preferably 200 to 600 parts by weight, relative to 100 parts by weight (solid content) of the resin component. In the present invention, by including the flame retardant in such a relatively high ratio, good performance in terms of heat resistance protection can be obtained.
[0020] The foaming agent of the present invention generally has the effect of generating a non-flammable gas in the event of a fire, foaming the resin component and the carbonizing agent which are being carbonized, and forming a carbonized heat insulating layer having pores. The foaming agent is not particularly limited as long as it has such an effect, and known foaming agents can be used. For example, melamine and its derivatives, dicyandiamide and its derivatives, azodicarbonamide, urea, thiourea, etc. can be mentioned. These can be used alone or in combination of two or more. The mixing ratio of the foaming agent is preferably 5 to 500 parts by weight, more preferably 30 to 200 parts by weight, relative to 100 parts by weight (solid content) of the resin component. By being in such a range, excellent foaming properties can be exhibited, and good performance in heat resistance protection can be obtained.
[0021] The carbonizing agent of the present invention generally has the effect of forming a thick carbonized heat insulating layer with excellent heat insulating properties by dehydrating and carbonizing itself as well as carbonizing the resin component due to fire. The carbonizing agent used in the present invention is not particularly limited as long as it has such an effect, and known carbonizing agents can be used. For example, polyhydric alcohols such as pentaerythritol, dipentaerythritol, and trimethylolpropane; starch, casein, etc. can be mentioned. These can be used alone or in combination of two or more. The mixing ratio of the carbonizing agent is preferably 5 to 600 parts by weight, more preferably 10 to 400 parts by weight, relative to 100 parts by weight (solid content) of the resin component. By being in such a range, it is possible to exert a dehydration cooling effect and a carbonized heat insulating layer forming effect, and obtain good performance in heat resistance protection.
[0022] The filler of the present invention generally has the effect of maintaining the strength of the carbonized heat insulating layer. In the present invention, examples of the filler include titanium dioxide, calcium carbonate, inorganic fibers, etc. These can be used alone or in combination of two or more. The mixing ratio of the filler is preferably 5 to 600 parts by weight, more preferably 10 to 400 parts by weight, per 100 parts by weight (solid content) of the resin component.
[0023] The thermally foamable coating material of the present invention may contain various additives as components other than those described above. Examples of such components include pigments, fibers, thickeners, film-forming assistants, leveling agents, wetting agents, plasticizers, antifreeze agents, pH adjusters, preservatives, antifungal agents, anti-algae agents, antibacterial agents, dispersants, defoamers, adsorbents, crosslinking agents, ultraviolet absorbers, antioxidants, catalysts, etc. Expandable substances such as expandable graphite and unexpanded vermiculite may also be contained.
[0024] The thickness of the thermally foamable covering material layer 2 of the present invention is set depending on the desired heat-resistant protective performance, but is preferably about 0.2 to 10 mm, and more preferably about 0.5 to 6 mm. By laminating such a thermally foamable covering material layer 2, excellent heat-resistant protective performance can be exhibited when exposed to high temperatures such as during a fire.
[0025] (Auxiliary parts) The auxiliary member 3 of the present invention is fixed to the base 1 and is an auxiliary member for measuring the film thickness of the thermally foamable coating material layer 2 laminated on the base 1.
[0026] The auxiliary member 3 is characterized by having a metal material at least on its upper surface (the surface opposite to the base surface). For example, a metal material or at least one material selected from resin, wood, fiber material, paper, etc., on which a metal material is laminated, can be used as the auxiliary member 3. Examples of the metal material include magnetic metals and non-magnetic metals, such as iron, steel, stainless steel, aluminum, copper, brass, etc. These materials can be used alone or in combination of two or more. In addition, the surfaces of these metal materials may be subjected to some surface treatment within a range that does not impair the effects of the present invention. By using such an auxiliary member 3, the thickness of the thermally foamable coating material layer 2 laminated on the base 1 can be easily measured by an electromagnetic or eddy current type thickness meter.
[0027] The auxiliary member 3 preferably has an area of 1 cm 2 More than 1cm (preferably 1cm 2 More than 25cm 2 Less than 1 cm, more preferably2 More than 10cm 2 The area and thickness are preferably 0.1 μm or more and 5 mm or less (more preferably 0.5 μm or more and 3 mm or less). In such a case, the film thickness can be stably measured. Furthermore, when the area and thickness satisfy the above ranges, the transfer of heat to the base 1 can be suppressed, and sufficient heat-resistant protection can be ensured.
[0028] The upper surface of the auxiliary member 3 is preferably flat, and may be, for example, a film, sheet, or plate. The planar shape is not particularly limited, and examples include a triangle, a square (rectangle, trapezoid, rhombus, etc.), a polygon, a circle, an ellipse, etc., and the corners may be rounded.
[0029] The method for fixing the auxiliary member 3 of the present invention may be appropriately determined depending on the base 1, and for example, an adhesive, a fastener, or the like may be used. 3 is an enlarged view of the covered structure of the present invention, showing an example of an auxiliary member 3 fixed with an adhesive 31. When fixing with adhesive 31, for example, adhesive 31 may be applied to the underside (base surface side) of base 1 and / or auxiliary member 3, and the auxiliary member may be attached to the base surface. Alternatively, an auxiliary member 3 with adhesive 31 pre-laminated on one side (for example, a metal tape) may be used.
[0030] 4(I) and 4(II) are cross-sectional views showing an example of the coated structure of the present invention. In FIG. 4, an auxiliary member 3 is fixed to a base 1 using a fastener 32, and a thermally foamable coating material layer 2 is laminated so as to cover the auxiliary member 3. FIG. 5 is an enlarged view of the coated structure of the present invention, showing an example of the auxiliary member 3 fixed with the fastener 32. In the case of fixing with the fastener 32, for example, a method of fixing by fitting the fastener 32 into a hole provided in the auxiliary member 3 (FIG. 5(I)), or a method of fixing with the auxiliary member 3 in which the auxiliary member 3 and the fastener 32 are previously joined and integrated (FIG. 5(II)), etc. may be mentioned. In addition, two or more fasteners 32 may be used (FIG. 5(III)). Furthermore, in the present invention, the adhesive 31 and the fastener 32 may be used in combination.
[0031] The fastener 32 is not particularly limited as long as it can be fixed to the substrate 1, and a plurality of fasteners 32 may be provided. The fastener 32 is preferably fixed by piercing the substrate 1, and its shape is preferably sharp. The fastener 32 may have a screw portion. The length (H32) of the fastener 32 is preferably 5 to 100 mm (more preferably 8 to 50 mm), and the thickness of the fastener 32 is preferably 0.5 to 5 mm (more preferably 1 to 4 mm). In this case, the auxiliary member 3 can be sufficiently fixed to the substrate 1. In particular, the auxiliary member 3 can be stably fixed even if the substrate 1 is made of a flexible material or an existing material that has deteriorated over time. As a result, when the coated structure of the present invention is exposed to high temperatures such as during a fire, the thermally foamable coating layer can stably foam and form a carbonized insulation layer, and the formed carbonized insulation layer can be prevented from falling off the substrate 1.
[0032] Furthermore, it is preferable that the length (H32) of the fastener 32 is shorter than the thickness of the base 1. Specifically, it is preferable that the length (H32) of the needle portion 32 is shorter than the thickness (H1) of the base 1 by 5 mm or more (more preferably 8 mm or more). In such a case, heat is less likely to be transferred to the base 1, and the desired heat-resistant protection can be sufficiently obtained.
[0033] The material of the fastener 32 is not particularly limited, and examples thereof include metal materials, resins, wood, etc. In the present invention, non-flammable materials are preferable, and metal materials are particularly preferable.
[0034] The configuration of the covering structure of the present invention will be specifically described below.
[0035] (Method of forming a covering structure) The covered structure of the present invention can be obtained, for example, by fixing an auxiliary member 3 to a base 1 and then applying a thermally foamable covering material to the base 1 to form a thermally foamable covering material layer 2.
[0036] The auxiliary member 3 is preferably fixed to the surface of the substrate 1 using an adhesive 31 and / or a fastener 32 so that the auxiliary member 3 fits along the surface of the substrate 1. This allows the auxiliary member 3 to be stably fixed to the substrate 1, and the thickness of the thermally foamable coating material layer can be stably measured. Furthermore, it is preferable to use multiple auxiliary members 3 depending on the shape and size of the substrate 1. This allows the formation of a thermally foamable coating material layer of uniform thickness.
[0037] The thermally foamable coating material layer 2 is formed by applying a thermally foamable coating material to the base 1 with the auxiliary member 3 fixed thereto. In applying the thermally foamable coating material, spray coating using a spray gun, airless spray gun, pressure feeder, etc., trowel coating, brush coating, roller coating, etc. can be used. During application, the viscosity can also be appropriately adjusted with a diluting solvent.
[0038] The thickness of the thermally foamable coating material layer 2 can be appropriately set depending on the heat-resistant protective performance, the application site, etc., but is usually about 0.1 to 20 mm, preferably about 0.3 to 10 mm. In coating the thermally foamable coating material, multiple coats can be applied so that the coating film has a predetermined thickness.
[0039] When the covering structure of the present invention is exposed to high temperatures such as during a fire, the anchor effect of the auxiliary member 3 allows the thermally foamable covering material layer 2 to foam stably and form a carbonized insulation layer, while preventing the formed carbonized insulation layer from falling off the substrate 1. In addition, the substrate 1 and the thermally foamable covering material layer 2, excluding the fixing portion of the auxiliary member 3, have excellent adhesion, and the desired heat resistance protection can be sufficiently obtained.
[0040] <Film thickness measurement method> In the coated structure of the present invention, the film thickness of the thermally foamable coating layer 2 laminated on the base 1 can be measured using an electromagnetic or eddy-current film thickness meter, as shown in Fig. 6. The auxiliary member 3 is fixed to the base 1, and the thermally foamable coating layer 2 is laminated so as to cover the auxiliary member 3. By measuring the distance X from the surface of the thermally foamable coating layer 2 to the auxiliary member 3, the film thickness of the thermally foamable coating layer 2 can be measured. EXAMPLES
[0041] The following examples will clarify the features of the present invention.
[0042] (Thermal foaming coating material) 250 parts by weight of acrylic resin solution (solid content 40% by weight) and 90 parts by weight of dilution solvent were added, and then mixed and stirred with a dissolver. Next, 100 parts by weight of melamine, 100 parts by weight of dipentaerythritol, 400 parts by weight of ammonium polyphosphate, and 120 parts by weight of titanium oxide were added and stirred until homogenized to prepare a thermally foamable coating material.
[0043] (Test Example 1) As shown in FIG. 2, aluminum tape [1.5 cm×1.5 cm×thickness 80 μm (aluminum layer 50 μm, adhesive layer 30 μm)] was attached and fixed as an auxiliary member to the base of a H-shaped steel frame 41 (H400×200×8×13 mm, length 1200 mm) coated with a 25 mm thick fiber-based insulation material. At this time, the auxiliary members were fixed at intervals of 300 mm in the length direction of the H-shaped steel frame 41. Next, the thermally foamable coating material was applied with a roller to form a thermally foamable coating layer, which was used as a test specimen. At this time, the thermally foamable coating layer was formed to a uniform thickness (3.7 mm) at the part of the test specimen where the auxiliary member was fixed, while measuring the film thickness using an eddy current type film thickness meter. The prepared specimens were subjected to a 3-hour heating test in accordance with the standard heating curve of ISO 834. As a result, the carbonized insulation layer was formed almost uniformly without falling off, and showed good heat resistance.
[0044] (Test Example 2) As shown in Fig. 7, the surface of the H-shaped steel frame 41 (H400 x 200 x 8 x 13 mm, length 1200 mm) was covered with a 25 mm thick fiber-based insulation material, and the auxiliary member with a fastener attached in advance [the auxiliary member shown in Fig. 5 (II) (steel, rectangular plate shape: 1.5 cm x 1.5 cm x thickness 0.6 mm, area 2.25 cm ] was placed on the base. 2The test specimens were then fixed in place by inserting fasteners (steel, 15 mm long, 1.2 mm thick). At this time, auxiliary members were fixed at 300 mm intervals along the length of the H-shaped steel frame 41. The thermally foamable coating material was then applied with a roller to form a thermally foamable coating layer, and the resulting test specimens were used. At this time, the thermally foamable coating layer was formed to a uniform thickness (3.7 mm) at the part of the test specimen where the auxiliary member was fixed, while measuring the coating thickness with an electromagnetic coating thickness meter. The prepared specimens were subjected to a 3-hour heating test in accordance with the standard heating curve of ISO 834. As a result, the carbonized insulation layer was formed almost uniformly without falling off, and showed good heat resistance.
Claims
1. A coated structure in which a thermally foamable coating material layer is laminated on a substrate, the substrate being a non-metallic material, the non-metallic material being a fiber-based insulation material or a foamed plastic insulation material, an auxiliary member being fixed to a surface of the substrate using a fastener, the auxiliary member having a metal material on at least its upper surface, The fastener is fixed to the base by piercing it, and a thermally foamable coating material layer is laminated on the base to cover the auxiliary member.
2. The auxiliary member has an area of 1 cm 2 2. The covering structure according to claim 1, wherein the thickness is 0.1 μm or more and 5 mm or less.
3. A covering structure as described in claim 1, characterized in that the fastener has a length of 5 to 100 mm and is shorter than the thickness of the base.
4. 4. A method for measuring a thickness of a thermally foamable coating layer in a coated structure according to claim 1, comprising measuring a distance from a surface of the thermally foamable coating layer to the auxiliary member by an electromagnetic or eddy-current type thickness meter.
Citation Information
Patent Citations
Fire resistant coating of structure of steel frame and the like
JP1989260139A
Hybrid fire-proof coated structure body and its fire-proof coating work method
JP1995259212A
Method for applying intumescent fireproof coating and method for controlling thickness of film
JP2003088799A
Method of measuring dry film thickness of coating material applied onto substrate other than metal
JP2004188402A
Process saving foaming fireproof coating material
JP2018159065A